2021
DOI: 10.2174/1570159x18666201119153807
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibitory Potential of Quercetin towards Alzheimer’s Disease - A Promising Natural Molecule or Fashion of the Day? - A Narrowed Review

Abstract: : Natural substances are known to have strong protective effects against neurodegenerative diseases. Among them, phenolic compounds, especially flavonoids, come to the fore with their neuroprotective effects. Since quercetin, which is found in many medicinal plants and foods, is also taken through diet, its physiological effects on humans are imperative. Many studies have been published up to date on the neuroprotective properties of quercetin, a flavanol derivative. However, there is no review published so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al, 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al, 2021;Long et al, 2020;Miglis et al, 2021;Orhan, 2021;Rocha-Brito et al, 2022;Romo-Nava et al, 2022; Premkumar et al, 2005) can achieve the effect of treating insomnia.…”
Section: Reverse Docking Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al, 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al, 2021;Long et al, 2020;Miglis et al, 2021;Orhan, 2021;Rocha-Brito et al, 2022;Romo-Nava et al, 2022; Premkumar et al, 2005) can achieve the effect of treating insomnia.…”
Section: Reverse Docking Resultsmentioning
confidence: 99%
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al., 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al., 2021; Long et al., 2020; Miglis et al., 2021; Orhan, 2021; Rocha‐Brito et al., 2022; Romo‐Nava et al., 2022; Su et al., 2021; Wang et al., 2022; Zhai et al., 2021), and relevant cell experiments or animal experiments have shown that quercetin has an impact on these nine proteins (Ceresa & Peterson, 2014; Cianci et al., 2015; Cuevas et al., 2011; Khodarahmi et al., 2019; Pakdel, 2018; Vieira & Saraiva, 2014). Insomnia is the most immediate symptom experienced by patients with Parkinson's syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…[80,81] In addition, flavonoids such as quercetin, vitexin, or kaempferol showed significant inhibitory effects on cholinesterases. [82][83][84]…”
Section: Ache At the Central Level Previous Studies Have Reported Thatmentioning
confidence: 99%
“…While its distribution was evidenced in the plasma, liver, heart, spleen, kidneys, and lungs, quercetin levels were non-detectable in the rat brain [326,327]. Hence, it has around 65% BBB permeability [321,328] and is absorbed in the stomach with 24-53% bioavailability [329]. The P-glycoprotein transporter, which is a BBB efflux transporter, has a high affinity for free, unaltered quercetin and greatly reduces its bioavailability by pumping quercetin away from the brain [51,330].…”
Section: Quercetin and Kaempferol In Common Herbsmentioning
confidence: 99%